Lecturer Attitudes on Cross-Cultural Practices in EFL Online Teaching - Nurhikmah, Andi; Syam, Anugerah Febrian; AP, Sumrah (Universitas Lancang Kuning, 2023)
Most studies on the link between cross-cultural values and language teaching conducted in online settings almost always draw on students’ perspectives, yet few focus on how the attitudes of higher education lecturers in the conduct of this program. Therefore, this study aims to investigate EFL lecturers’ attitudes toward cross-cultural practices during EFL online teaching. A qualitative approach with observation and semi-structured interviews via face-to-face and online meetings is used to collect the data in this research. Using purposive sampling, this study employs four EFL lecturers from Muhammadiyah university as selected participants based on their experiences in teaching cultural-integrated classes at both offline and online schemes. The study discovered that EFL lecturers understand cross-cultural practices in EFL online teaching to be associated with personality traits, language roles, and understanding of local culture as a way to incorporate cross-cultural knowledge into their teaching. To foster effective interaction in the class, lecturers focus on conveying opinions and maintaining communication by understanding with whom to speak, where to speak, and ways to speak. These essences and fundamental attributes influence cross-cultural practices in EFL online teaching. The study reveals that cultural differences, incorrect expressions such as a lack of appropriate word choices, and a mismatch of verbal and nonverbal language can cause cross-cultural teaching barriers. Furthermore, the need to create an authentic environment, increase intercultural knowledge, and eliminate cultural stereotypes is to be addressed as cross-cultural teaching strategies in an EFL online teaching context.